Performance of lactating goats fed diets containing inactive dry yeast - Ludmila Couto Gomes; Claudete Regina Alcalde; Francisco de Assis Fonseca de Macedo; Geraldo Tadeu dos Santos; Altair Antônio Valloto; Luciano Soares de Lima; Bruna Susan de Labio Molina (Revista Brasileira de Zootecnia, 2012)
Twenty-four Saanen goats (15 multiparous and 9 primiparous) from 21 days prepartum to 200 days in lactation were used to evaluate milk yield and composition. Animals were randomly distributed in a 3 × 2 factorial arrangement (3 diets × 2 parity orders) and fed a 40:60 forage:concentrate diet composed of soybean meal, soybean meal + dry yeast or dry yeast as protein source, plus ground corn, mineral supplement and corn silage. The protein source did not influence the body weight of pre and postpartum goats. Prepartum, postpartum and postpeak dry matter intake (DMI) were not altered by diets. However, goats fed the diet containing dry yeast as protein source had lower DMI in late lactation. Milk yield and feed efficiency were not affected by diets. Milk components, acidity and somatic cell count were not influenced by diets during all lactation phases. However, fat and total solid contents postpartum were higher for primiparous goats and somatic cell count postpeak was lower for multiparous goats. Dry yeast can be used to replace soybean meal in diets for lactating Saanen goats.